UPAYA PENURUNAN LOGAM BERAT PB PADA KERANG HIJAU UNTUK MENINGKATKAN KEAMANAN PANGAN PRODUK UNGGULAN DI DESA BANYUURIP KECAMATAN UJUNG PANGKAH KABUPATEN GRESIK - Aminin Aminin; Andi Rahmad Rahim; Sa’idah Luthfiyah (Universitas Muhammadiyah Gresik, 2021)
The existance of metal pollution detected in water and green mussel’s flesh in Bayuurip Village, Glagah Sub-District, Gresik Regency, had a big impact in production and food security in that region. According to 3 years data (2018-2020), the production of green mussels was decreased significantly. Harvest was usually reach to 5-7 tons/day, nevertheless, currently only 1.5-2 tons/day. The size of yields were smaller, the harvest was usually in <5 cm; in size >5-7 cm are very scarce. Besides, the size of green mussels influence its selling price. Although the Pb levels were still lower than threshold from the goverment, nevertheless, the issue of their existance was a major concern, especialy in the decrease of market demand and the increase of citizens awareness of food security. For this reason, through The Internal Community Service Program of UMG, was expected to provide the information to citizens that green mussels are still worth consuming and safety, especially with the use of depuration method; increase the local society awareness to maintain the hygiene, implement depuration technology to keep food product safe and securable. The external expectation of this program is to develop an independent local community, in social economy. This activity was scheduled in Bayuurip Village, Ujung Pangkah Sub-district, Gresik Regency, with several purposes: (1) Applied the depuration technology manipulation to reduce metal pollution in green mussels flesh; (2) Increase the economic value of featured product (green mussels) and its food safety; (3) Develop positive opinion that green mussels are safe to consume after depuration treatment.